2011
DOI: 10.1042/cbi20100118
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic effect of eugenol in human colon cancer cell lines

Abstract: Eugenol, a natural compound available in honey and various plants extracts including cloves and Magnoliae flos, is exploited for various medicinal applications. Since most of the drugs used in the cancer are apoptotic inducers, the apoptotic effect and anticancer mechanism of eugenol were investigated against colon cancer cells. Antiproliferative effect was estimated using MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide assay]. Earlier events like MMP (mitochondrial membrane potential), thio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(95 citation statements)
references
References 18 publications
3
87
0
5
Order By: Relevance
“…Promoting apoptosis and suppressing cell proliferation are examples of mechanism by which honey could exhibit its anti-cancer property Jaganathan et al, 2011;Jaganathan, 2012;Ahmed and Othman, 2013). Despite accumulating evidence suggesting the potential of honeys in combating colorectal cancer, there is not much evidence regarding local Gelam honey having anticancer effect and especially colon cancer in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Promoting apoptosis and suppressing cell proliferation are examples of mechanism by which honey could exhibit its anti-cancer property Jaganathan et al, 2011;Jaganathan, 2012;Ahmed and Othman, 2013). Despite accumulating evidence suggesting the potential of honeys in combating colorectal cancer, there is not much evidence regarding local Gelam honey having anticancer effect and especially colon cancer in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Tualang honey which consisted of high flavonoids, phenolic acid and hydroxymethylfurfural was also reported to cause apoptosis of breast and cervical cancer cells (Fauzi et al, 2011). A bioactive compound extracted from honey such as eugenol showed increased apoptosis of colon cancer cells by arresting cell cycle at sub-G1 phase and activation of p53 and caspase-3 (Jaganathan et al, 2010). Chrysin which is one of the polyphenols in honey also induced apoptosis on melanoma cells by activation of caspases cascade pathway (Pichichero et al, 2011).…”
Section: Malaysia Is Known For Its Wide Variety Of Honeys Either Honementioning
confidence: 99%
“…EU 1 and its derivatives have been reported to inhibit colon cancer cell proliferation by arresting the cells in sub G1 phase, augment reactive oxygen species (ROS) levels that result in DNA fragmentation, which is a hallmark of apoptosis. It has been reported that EU is a phenolic compound that induces apoptosis in human colon cancer cells [16]. The antiproliferative activity of EU against melanoma [17], leukemia [18], gastric [19], skin tumor [20], and prostate cancer [21] cells has been confirmed by many researchers.…”
Section: Introductionmentioning
confidence: 72%
“…The results demonstrated molecular mechanism of EU -induced apoptosis in human colon cancer cells. This research will further enhance EU as a potential chemopreventive agent against of colon cancer [16]. Another research was conducted that EU combine with canola oil showed an antiproliferative effect against colon cancer cell lines depending on the concentration and the cell lines used.…”
Section: Fadilah Et Almentioning
confidence: 99%